SIKAP IBU, DUKUNGAN KELUARGA, DAN PERNIKAHAN DINI DENGAN KEBERHASILAN PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS KESUMADADI: The Correlation Between Mother's Attitudes, Family Relations and Early Marriage with the Success of Exclusive Breastfeeding in the Working Area of Kesumadadi Public Health Center - Arrozi, Zakia Ulfa; Khairani, Masayu Dian; Muharramah, Alifiyanti; Putri, Nopi Anggista (Media Gizi Pangan, 2024)
Giving infants under six months of age only breast milk and no other fluids is known as exclusive breastfeeding. In Indonesia, 56.9% of women exclusively breastfeed, while 75.37% of women exclusively breastfeed in the province of Lampung. Aside from knowledge, attitudes, and behavior, factors that contribute to the lack of exclusive breastfeeding include productive age, employment, beliefs, family support, and health professionals. This research objective was to determine the correlation between maternal attitudes, family support, and early marriage with the success of exclusive breastfeeding in the working area of Kesumadadi Public Health Center in 2023.The type of research used is quantitative observational, with a cross- sectional research design. Sampling used a simple random sampling technique using the interview method. The statistical test used is chi-square with a degree of 95%.This study was carried out in the Kesumadadi Community Health Center Working Area between October 2023 and January 2024. The study's findings showed that 36 moms (or59%) had completed high school, 47 women (or77%) were stay-at-home moms, and 58 mothers (or95.1%) were adult (19-45 years old). In the Kesumadadi Public Health Center working area, statistical tests reveal a strong association between early marriage (p=0.039), family support (p=0.002), and mother attitudes (p=0.037) and the effectiveness of exclusive breastfeeding. It is hoped that moms will be able to continue exclusively breastfeeding their children, and that relatives will be able to assist these mothers financially and emotionally.